Sheltering hopes: empowering lives, supporting the homeless - Muhamad Afiq Zulkifli, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Empowering Lives, Supporting the Homeless is a comprehensive and compassionate volunteer programme designed to address the multiple challenges facing homeless individuals and communities under the motto "Homeless We Cares." This initiative aims not only to provide homeless people with necessities but also to empower them emotionally and spiritually to regain control of their lives and become self-sufficient. At the same time, the programme has taught students the importance of showing compassion and providing moral support from society to this group to make them more resilient and persistent. The programme is based on empathy and collaboration between non-governmental organisations (NGOs), local universities and government agencies, with a team of 35 volunteers working in various homeless communities around Kuala Lumpur. In addition, Sheltering Hopes plans to implement this initiative by engaging with homeless shelters, connecting with the local community, and raising awareness about the needs of this vulnerable group. Sheltering Hopes strives to break the cycle of homelessness and alleviate the social and economic burdens by providing hope to these communities so that they continue to look for a glimmer of light at the end of the dark tunnel. The immediate impact of this programme is to sensitise students to get involved in their communities and encourage them to develop into young people who serve society and contribute not only with academic qualifications but also to help promote a harmonious society.